SEMIOTIKA TANDA INFOGRAFIS KOMISI PEMBERANTASAN KORUPSI (KPK) - Arifianto, Pungky Febi (Jurnal Bahasa Rupa, 2018)
In term of its presentation of data, qualitative descriptive research is implemented as the method. To interpret the handling of corruption conducted by Indonesias Corruption Eradication Commission, Charles S. Piercesâ theory of signs classification in icon, index, and symbol is utilized as the approach. Disclosure of meaning the signs itself applies of Rolland Barthesâs connotation interpretations in significance. The Five Codes in significances are divided into Hermeneutic, Proairetic, Semantic, Symbolic, and Cultural. Visual infographic analysis in corruptionâs handling by Indonesias Corruption Eradication Commission is expected for being able to give a discourse in semiotic interpretation to signs and meaning in infographics. Theoretically, the purpose of this analysis will give depiction about a scientific approach to visual communication design theory in sending message through sign-system in each visual elements in infographics.